2017
DOI: 10.1002/ird.2111
|View full text |Cite
|
Sign up to set email alerts
|

Field Study of Variable Rate Irrigation Management in Humid Climates

Abstract: Comparison of variable rate irrigation (VRI) management with uniform rate irrigation (URI) management in soybean and corn crops was studied for 2 years in Stoneville, Mississippi, USA. The experiments were conducted on two 6.7 ha fields. Each of them was equally split into two sectors. VRI management was performed in one sector and URI management in the other. A centre pivot VRI system was used for delivering irrigation water. Soil apparent electrical conductivity (EC) of the fields was used to delineate VRI m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 45 publications
(40 reference statements)
2
35
1
Order By: Relevance
“…Compared to the uniform application, VRI increases crop productivity. The results comparing the water productivity of sorghum and corn showed that there was more than 20% increase in water productivity for both crops using VRI [35]. Another study conducted in a 4-ha field, VRI resulted in a significant difference in corn yield in a dry year.…”
Section: Impact Of Variable-rate Irrigationmentioning
confidence: 94%
See 1 more Smart Citation
“…Compared to the uniform application, VRI increases crop productivity. The results comparing the water productivity of sorghum and corn showed that there was more than 20% increase in water productivity for both crops using VRI [35]. Another study conducted in a 4-ha field, VRI resulted in a significant difference in corn yield in a dry year.…”
Section: Impact Of Variable-rate Irrigationmentioning
confidence: 94%
“…The basic requirements for the VRI technology are sensors and spatial information, prescription maps and a system to incorporate VRI prescription (e.g., LEPA, lateral irrigation, etc.) to apply in the field [35]. At present, there are several irrigation technologies for conservation irrigation, such as sprinkler, drip, and other micro-irrigation systems but limited site-specific studies have been done [30,[36][37][38].…”
Section: Variable-rate Irrigation Technologiesmentioning
confidence: 99%
“…Significant crop yield increases or reduction in water withdrawals resulting from VRI adoption were not observed in most studies. However, Sui and Yan (2017) found reduction in water withdrawals with VRI compared to a uniform irrigation method. Most of these studies, except for Barker et al (2018b), have been conducted at smaller scales, which may or may not be representative of commercial-field-scale agricultural production.…”
Section: Introductionmentioning
confidence: 90%
“…A number of field studies on VRI have been conducted to quantify the benefits of VRI (Stone et al, 2015;Stone and Sadler, 2016;Barker et al, 2018b;Sui and Yan, 2017). Significant crop yield increases or reduction in water withdrawals resulting from VRI adoption were not observed in most studies.…”
Section: Introductionmentioning
confidence: 99%
“…In the second year, VRI treatment water application depths ranged from 18% less to 10% greater water application. In Mississippi, Sui and Yan (2017) compared VRI and UI for corn and soybean production and reported VRI used 25% less water with no overall significant difference in yields.…”
mentioning
confidence: 99%